Visual Literacy: Awareness of Primary School Teacher Education Students - Siti Nurwita Sekar Suci; Sekar Purbarini Kawuryan; Dholina Inang Pambudi (MIMBAR PGSD Undiksha, 2024)
This research was motivated by the emergence of a situation of lack of ability to interpret visual media displayed during learning. This study aims to analyze the level of awareness of PGSD students in relation to visual literacy. This research applied a descriptive quantitative approach with a survey as the main method. A total of 54 PGSD UAD students class of 2023 were selected as samples, and data were obtained through questionnaires distributed using Google Forms. The data analysis technique applied descriptive analysis with the help of Microsoft Excel. The findings of the study show that the level of visual literacy skills of PGSD students is generally in the high category. This indicates that students have the awareness to identify, analyze, review, utilize, and produce visual representations and media. However, there are a number of aspects that indicate a low level of visual literacy of students. The latest information in this study implies that the campus can help provide services or seminars to students related to 1) evaluating images as visual communication, 2) evaluating textual information and image sources, 3) getting used to designing and using visual materials that are useful for learning in elementary schools, and 4) the ability to know the license of each image accessed and used.